KOMUNIKASI ANTARPRIBADI PIMPINAN TERHADAP KARYAWAN BERPERSPEKTIF GENDER - Ade Irma (Pusat Studi Wanita UIN Ar-Raniry, 2018)
The background of study was conducted under considerations that any organization needs togetherness in working atmosphere. One of the strategy to reach this is through a leader interpersonal communication based on gender perspectives. The leader interpersonal communication has very important role in one organization,it is because interpersonal communication occurs as human nature, face to face, and very effective in changing human perspectives, opinion, and attitudes. That is why the writer recommended to maintain the leader interpersonal communication which has gender perspective in minds frequently in order to achieve togetherness.